Batik’s Pattern Recognition and Generation: Review and Challenges - Sri Arsa, Dewa Made; Susila, Anak Agung Ngurah Hary; Dewi, Desak Ayu Sista; Sutramiani, Ni Putu; Darma, I Wayan Agus Surya (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2022)
Batik is one of cultural heritage acknowledged by UNESCO. Intelligence system comes as one of solution to take parts on preservation programs of this heritage. This study explores the current state of the art in application of artificial intelligence on Batik images. This research provides a systematic investigation and present the current progress and hot issues in recognition and generation area for Batik images. Furthermore, this research also presents several Batik data sets and their state of the art. As a result of the review, we are projecting several future works in the discussion.